2020
DOI: 10.5552/drvind.2020.1912
|View full text |Cite
|
Sign up to set email alerts
|

Weath ering Performance of Beech Wood Coated with Acrylic Paint Containing UV Stabilizers of Dihydroxy Benzophenone and Nano Zinc Oxide

Abstract: In this study, the effect of UV stabilizers (dihydroxy benzophenone and nano zinc oxide) on the weathering degradation of water-based acrylic coating on beech wood was investigated. The wood specimens were coated by brush and then weathered naturally for six months. The obtained results showed that the use of nano zinc oxide reduced color changes and mold growth on the surface of weathered samples. However, the results of contact angle, pull-off adhesion, colorimeter and FTIR revealed that the dihydroxyl benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Acrylic varnishes have interesting properties, as they are available in water-borne formulations and are therefore considered less toxic than solvent-borne products. In general, acrylic coatings show a quite interesting colour stability, but they are sensitive to mold fungi on the wood surface during weathering (Akbarnezhad et al 2020) and for this reason increasing their resistance to biotic attack is a goal to be pursued. Water repellent coatings can contribute to its resistance, but in this case a sufficient water vapour permeability is necessary to allow moisture escaping from the wood surface after a wetting event (Gibbons et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acrylic varnishes have interesting properties, as they are available in water-borne formulations and are therefore considered less toxic than solvent-borne products. In general, acrylic coatings show a quite interesting colour stability, but they are sensitive to mold fungi on the wood surface during weathering (Akbarnezhad et al 2020) and for this reason increasing their resistance to biotic attack is a goal to be pursued. Water repellent coatings can contribute to its resistance, but in this case a sufficient water vapour permeability is necessary to allow moisture escaping from the wood surface after a wetting event (Gibbons et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…5 the FTIR spectra of untreated wood (Virgin wood), pure acrylic resin (Av pure) as well as coated samples (Av on wood, Av-5CNC and Av-5LN) are shown. IR band assignments for beech wood were listed according to Bodîrlau et al (2008) while acrylic IR band assignments were found in Rao et al (2019) and Akbarnezhad et al (2020). After wood coating, the IR bands which are exclusively attributed to…”
Section: Ftir Spectroscopy and Ftir Mapping Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they found that the chemical structure of the coating becomes more stable to accelerated weathering after the addition of organic UV absorbers with increasing bamboo durability. However, Akbarnezhad et al [ 83 ] found that bezophenone-modified acrylic coating did not reduce the impact of natural weathering on beech wood. The efficiency of UV absorbers is determined by their absorption properties, concentration in the coating, coating thickness, chemical interaction with the binder, and other additives in the coating during photodegradation [ 69 ].…”
Section: Protection With Coatingsmentioning
confidence: 99%
“…Moya et al [ 90 ] found that TiO 2 nanoparticles added into the varnish reduced the colour change of tropical wood species during natural and accelerated weathering. Akbarnezhad et al [ 83 ] found that an acrylate coating with ZnO nanoparticles reduced colour change and mould growth on beech wood during natural weathering. Moreover, studies have also shown that the combined protection of coatings with UV absorbers (organic and inorganic) and HALS has a positive effect on the protection of wood from UV radiation.…”
Section: Protection With Coatingsmentioning
confidence: 99%